Effect of polysilane addition on spark plasma sintering and superconducting properties of MgB2 bulks. Issue 21 (1st November 2022) - Sandu, V.; Aldica, G.V.; Grigoroscuta, M.A.; Burdusel, M.; Pasuk, I.; Ching, Y.C.; Ionescu, A.M.; Badica, P.
Abstract: Polycrystalline MgB2 bulk samples were produced by ex-situ spark plasma sintering (SPS) using the oxygen-free preceramic polymer additive poly(dimethylsilane) as a source for carbon doping and as a sintering aid. Two major effects were identified. One is the significant enhancement of the densification kinetics during sintering for all tested compositions. The second one is the improvement of the high field critical current density for a certain level of the poly(dimethylsilane) addition.